Effects of the Discharge Parameters on the Efficiency and Stability of Ambient Metastable-Induced Desorption Ionization - 张晓天 陈池来 刘友江 王泓伟 张乐华 孔德义 Mario CHAVARRIA (Plasma science & technology, 2015)
Ionization efficiency is an important factor for ion sources in mass spectrometry and ion mobility spectrometry.Using helium as the discharge gas,acetone as the sample,and high-field asymmetric ion mobility spectrometry（FAIMS） as the ion detection method,this work investigates in detail the effects of discharge parameters on the efficiency of ambient metastableinduced desorption ionization（AMDI） at atmospheric pressure.The results indicate that the discharge power and gas flow rate are both significantly correlated with the ionization efficiency.Specifically,an increase in the applied discharge power leads to a rapid increase in the ionization efficiency,which gradually reaches equilibrium due to ion saturation.Moreover,when the discharge voltage is fixed at 2.1 kV,a maximum efficiency can be achieved at the flow rate of 9.0 m/s.This study provides a foundation for the design and application of AMDI for on-line detection with mass spectrometry and ion mobility spectrometry.